Breeding SCN-resistant soybean lines with improved oil and protein contents - Lian, Yun; Lei, Chenfang; Han, Dongwei; Yuan, Ming; Lu, Weiguo (Frontiers in Plant Science, 2025)
Soybean cyst nematode (SCN) disease caused by Heterodera glycines is one of the most devastating diseases in soybean (Glycine max L.) and results in significant yield losses annually worldwide. Breeding crops for resistance is an eco-friendly approach to minimize these losses. In this study, SCN-resistant germplasm with excellent agronomic traits was obtained through cross-breeding between resistant germplasm sources and local cultivars that were high-yielding but susceptible to SCN in China’s two major soybean-growing regions. Using the single seed descent method, plants with favorable agronomic traits were selected and then planted into rows to raise seeds for marker assays and environmental-controlled bioassays. Finally, three lines from Northeast China and three from the Huang-Huai Valleys, all harboring resistance to races 1, 3, and 5, were selected. Their 100-seed weight ranged from 18.91 g to 21.6 g. The average oil contents of the three high-oil-content lines (QingF6-67, QingF6-98, and QingF6-99) from Northeast China ranged from 19.96% to 22.74%. The average protein contents of the three lines (HHF7-3-10, HHF7-6-6, and HHF7-6-10) from the Huang-Huai Valleys ranged from 42.3% to 43.5%. These six resistant lines, which have increased seed oil or protein contents, could be used as resistant cultivars against SCN or advanced donor parents in soybean breeding programs.